Impact of land cover changes on carbon stock trends in Kenya for spatial implementation of REDD+ policy - Nyamari, Nicodemus (2021)
Nyamari, N., & Cabral, P. (2021). Impact of land cover changes on carbon stock trends in Kenya for spatial implementation of REDD+ policy. Applied Geography, 133, 1-12. [102479]. https://doi.org/10.1016/j.apgeog.2021.102479